Association of the human platelet antigens polymorphisms with platelet count in patients with COVID-19 - Ghaffari, Kazem; Rad, Mahsa Ashrafi; Moradi Hasan-Abad, Amin; Khosravi, Mersedeh; Benvidi, Arefeh; Iraji, Mahsa; Khargh, Heidar Ali Heidari; Ghasemi, Ali (Frontiers in Medicine, 2023)
Polymorphism in human platelet antigen (HPA)-1 and HPA-3 (GPIIb/IIIa), HPA-2 (GPIb/IX), HPA-4 (GPIIIa), HPA-5 (GPIa/IIa), & HPA-15 (CD109) was investigated in 86 Covid-19-infected patients with thrombocytopenia (Group A) and 136 Covid-19-infected patients without thrombocytopenia (Group B). HPA genotyping was done by the sequence-specific primers PCR method. Lower HPA-3a and higher HPA-3b (P=0.028) allele frequencies were seen in Group A than in Group B, and homozygosity for HPA 3b (P=0.038) alleles was more prevalent in Group A than in Group B. The allele and genotype distributions of the other HPA polymorphic variants were similar between the two groups. Univariate analysis identified the CCGGGC (P = 0.016) combined genotype to be negatively associated & the TCGGGC (P=0.003) and CCGGGC (P=0.003) to be positively associated with thrombocytopenia. The frequency of anti-HPA-1a and anti-HPA-3a antibodies was significantly higher in all patients compared to other anti-HPAs antibodies (P < 0.05). These results highlight the role of HPAs in the thrombocytopenia of Covid-19 infected patients. This is the first evidence demonstrating the differential association of the six common HPA gene variants and specific HPA genotype combinations with thrombocytopenia in Covid-19-infected patients.